Evaluation of the implementation of the learning program Design Modeling and Building Information SMK Negeri 1 Bengkalis - Septia Rahman; Ari Syaiful Rahman Arifin; Fahmi Rizal; M Giatman (JETL (Journal of Education, Teaching and Learning), 2025)
The rapid development of the Architecture, Engineering, and Construction industry has led to the increasing adoption of Building Information Modeling as a critical skill for future professionals. However, vocational high schools in Indonesia, including SMK Negeri 1 Bengkalis, often face challenges in integrating BIM-based learning due to limited resources, conventional teaching approaches, and lack of industry alignment. This study aims to evaluate the implementation of the Design Modeling and Building Information learning program at SMK Negeri 1 Bengkalis by examining three key aspects: planning, implementation, and assessment. The research used a quantitative descriptive method with survey instruments distributed to teachers and students. Data were collected through questionnaires, observations, and document analysis. The results show that the planning aspect received an average score of 88.8%, categorized as Good, with strengths in lesson planning and curriculum structure. The implementation aspect scored 82%, also Good, though student engagement and use of technology need improvement. The assessment aspect averaged 85%, with competency achievement rated Very Good, yet feedback and follow-up practices remain underdeveloped. In conclusion, the learning program has been generally well implemented, but further enhancement is needed in integrating digital tools, strengthening industry relevance, and promoting student-centered learning. These improvements are crucial for aligning vocational education with evolving AEC industry demands